PENGGUNAAN MEDIA WORD WOLL UNTUK MENINGKATKAN PENGUASAAN ANTONIM PADA SISWA SEKOLAH DASAR - Hannik Masruroh; Aini Eka Damayanti; Endang Noerhartati; Neza Pratama Yulianti Putri; Rika Wahyu Nur Hayati; Sesilia Intan Maharani (STKIP Subang, 2026)
At the elementary school level, teaching antonyms can be tedious and involve rote memorization, leading to boredom, lack of enthusiasm, and difficulty remembering and using words. This study explores the effectiveness of the Wordwall platform in improving antonym understanding among elementary school students. The method used is a qualitative descriptive approach based on a literature review, using data from leading journals, both national and international. Through a library study approach, scientific journal literature was used as a reference for the last year of publication in 2023–2025. The analysis was conducted through content analysis, which began with data identification, coding, interpretation, and drawing conclusions. The research findings indicate that Wordwall has a positive influence on antonym learning by increasing student motivation, engagement, and focus, as well as strengthening memory and conceptual understanding through fun and repetitive activities. The success of Wordwall is largely determined by the teacher's role in designing materials and connecting additional activities. Thus, Wordwall proves to be an effective and appropriate digital learning tool for elementary school students.Keywords: Wordwall, Elementary School, Antonym Learning, Indonesia